Central Macular Thickness in Uneventful Phacoemulsification Employing Optical Coherence Tomography - Ranabhat, Sudha; Byanju, Raghunandan; Pradhan, Sangita; Khadka, Simanta; Lamichhane, Benju (Journal of Institute of Medicine Nepal, 2022)
Introduction Cataract is the most common cause of blindness affecting the global population which can be cured by phacoemulsification surgery. The study aims to evaluate the central macular thickness following uneventful phacoemulsification surgery and analyze its relation to effective phacoemulsification time. Methods This prospective study comprised of 63 subjects with absence of ocular/systemic comorbidities, diagnosed as age-related cataract on the basis of lens opacities classification system III and undergoing uneventful phacoemulsification surgery with capsular bag intraocular lens implantation. The central macular thickness was evaluated using optical coherence tomography at preoperative, 1st day, 1st week and 5th week postoperatively. Effective phacoemulsification time was measured intraoperatively. Results The mean age was documented to be 65.73±9 years (45-88 years) with mean effective phacoemulsification time of 17.95±14.01 seconds (3-59 seconds). Best corrected visual acuity improved significantly postoperatively(p<0.05). Mean central macular thickness increased significantly on the 5th postoperative week compared to preoperative assessment (p<0.002). No significant association was detected between patient’s age and preoperative and postoperative central macular thickness. No correlations were observed between effective phacoemulsification time and central macular thickness. Significant association was not noted between central macular thickness and best corrected visual acuity on preoperative and postoperative examinations (p>0.05). Conclusion There is a decrease in central macular thickness on the 1st day and 1st week postoperatively followed by a significant increase on the 5th postoperative week compared to the preoperative period, which is independent of effective phacoemulsification time. Increase in central macular thickness in the postoperative period did not affect the quality of vision.